Knowledge socialization: strategies in the field of nanoscience and nanotechnology in venezuela (2013)
Since 2009, the Venezuelan Network of Nanotechnology has developed some activities for the dissemination of this knowledge area, and also promoted joint working initiatives between members interested in advancing in such task. This paper presents an overview of the activities of the network and other groups related to the subject, and also present the network strategies for the future which arises in the context of a broad notion of the meaning of socialization of knowledge as the axis of transformation of society.